In-situ construction of electrodeposited polyaniline/nickel-iron oxyhydroxide stabilized on nickel foam for efficient oxygen evolution reaction at high current densities. (19th September 2022) - Xue, Zhili; Wang, Yuanqiang; Yang, Mengru; Wang, Ting; Zhu, Haozhen; Rui, Yichuan; Wu, Shujing; An, Wei
Abstract: We report an in-situ construction method for the NiFe-based oxyhydroxide OER electrocatalyst supported on the nickel foam (NF) substrate with the polyaniline (PANI) interlayer by sequential electrochemical deposition steps (NF/PANI/NiFe–OH). The ultra-thin nanosheet for the nickel-iron (oxy)hydroxides tightly grown on the porous PANI exhibits the enhanced electrochemical characteristics associated with the promotion roles of the PANI layer, which increases the number of active sites, facilitates the charge transfer, and accelerates water transport across the interfaces of the electrode. The as-prepared NF/PANI/NiFe–OH has reliable lower overpotentials of 260, 340, and 490 mV without iR -correction at 50, 100, and 200 mA cm −2 of high current densities, respectively. The smaller Tafel slope, larger ECSA, and TOF values of the electrode reveal its high intrinsic activity. Moreover, the electrode shows good stability and durability without the damage of morphology, change of surface chemical state, and substantial loss of active components at high current density. Graphical abstract: The OER mechanism and stability of electrodeposited polyaniline/nickel-iron oxyhydroxide stabilized on nickel foam (NF/PANI/NiFe-OH). Image 1 Highlights: The in-situ construction method for electrodeposited PANI/NiFe–OH is used. The PANI interlayer improves the surface structure and chemical state of NiFe–OH. The PANI/NiFe–OH electrode has superior OER activity compared to NiFe–OH. The promoting mechanism of PANI on electrochemical OER performance is determined.